INFORMATION RETRIEVAL SYSTEM PADA FILE PENCARIAN DOKUMEN TESIS BERBASIS TEXT MENGGUNAKAN METODE VECTOR SPACE MODEL - Fauzi, Ahmad; Ginabila, Ginabila (Jurnal Pilar Nusa Mandiri, 2019)
Speed and density in the process of finding documents and information has become mandatory, contained in information systems, to facilitate the search process or find documents and information needed, it is called information retrieval or information retrieval system, implementation of the theory applied in this study using the model method vector space, the purpose of this study is to provide general exposure to the process of finding digital documents. With the token and indexing process so that the results of the masses are found in the database using keywords, so the system will search according to the keywords input into the system, and will be compared with the data contained in the database, so that it can produce the correct information.